Decoding Pure Rotational Molecular Spectra for Asymmetric Molecules. (17th September 2012) - Cooke, S. A.; Ohring, P.
Abstract : Rotational spectroscopy can provide insights of unparalleled precision with respect to the wavefunctions of molecular systems that have relevance in fields as diverse as astronomy and biology. In this paper, we demonstrate how asymmetric molecular pure rotational spectra may be analyzed "pictorially" and with simple formulae. It is shown that the interpretation of such spectra relies heavily upon pattern recognition. The presentation of some common spectral line positions in near-prolate asymmetric rotational spectra provides a means by which spectral assignment, and approximate rotational constant determination, may be usefully explored. To aid in this endeavor we have created a supporting, free, web page and mobile web page.